Design of a DC-AC Link Converter for 500W Residential Wind Generator - Muhida, Riza; Zaidi, Ahmad Firdaus A.; Tamsir, Afzeri; Irawan, Rudi (Journal of Mechatronics, Electrical Power and Vehicular Technology, 2012)
Â As one of alternative sources of renewable energy, wind energy has an excellence prospect in Indonesia, particularly in coastal and hilly areas which have potential wind to generate electricity for residential uses. There is urgent need to locally develop low cost inverter of wind generator system for residential use. Recent developments in power electronic converters and embedded computing allow improvement of power electronic converter devices that enable integration of microcontrollers in its design. In this project, an inverter circuit with suitable control scheme design was developed. The circuit was to be used with a selected topology of Wind Energy Conversion System (WECS) to convert electricity generated by a 500W direct-drive permanent magnet type wind generator which is typical for residential use. From single phase AC output of the generator, a rectifier circuit is designed to convert AC to DC voltage. Then a DC-DC boost converter is used to step up the voltage to a nominal DC voltage suitable for domestic use. The proposed inverter then will convert the DC voltage to sinusoidal AC. The duty cycle of sinusoidal Pulse-Width Modulated (SPWM) signal controlling switches in the inverter was generated by a microcontroller. The lab-scale experimental rig involves simulation of wind generator by running a geared DC motor coupled with 500W wind generator where the prototype circuit was connected at the generator output. The experimental circuit produced single phase 240V sinusoidal AC voltage with frequency of 50Hz. Measured total harmonics distortion (THD) of the voltage across load was 4.0% which is within the limit of 5% as recommended by IEEE Standard 519-1992.